The effect of using McCarthy model on learning the skill of passing and ball control in football - بلال محمود; لؤي سالمه; أمين الحاج حسن (Latakia University Journal -Medical Sciences Series, 2023)
Finding modern strategies, methods and methods in teaching sports skills has become a necessity for the success of the educational process, as modern learning methods are based on making the learner more active and positive. The research aims to identify the impact of using the McCarthy model in learning the skill of passing and ball control in football. The research hypotheses included that there is a positive effect of the McCarthy model in teaching the skills of passing and ball control in football. The researcher used the experimental method by designing (the two equal groups with a pre and post test) in order to suit the nature of the problem and achieve the research objectives. As for the research sample, it included the first year students of the Faculty of Physical Education, Tishreen University, who numbered (40) students. The most important results of the research were the superiority of the experimental group that used the McCarthy model over the control group that used the command method, and there was a preference for the McCarthy model over the command method in the post tests for the skills of passing and ball control. The researcher recommended emphasizing the importance of the McCarthy model in teaching basic skills in football, and the necessity of conducting scientific seminars on how to apply this model to other games.